Sistem Pendukung Keputusan Pemilihan Kost Di Sekitaran Kampus Universitas Flores Menggunakan Metode Simple Additive Weighting (Saw) - Titin Dhiki (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The problem in this study is that students still have difficulty in choosing a boarding house based on the criteria for the rental price of the boarding house, available facilities, security and cleanliness. The purpose of this study is to determine the selection of boarding houses using the simple additive weighting (SAW) method. The research method used is a type of quantitative research that is descriptive. The data collection techniques used are unstructured interviews and questionnaires using the Guttman scale. The system development method uses waterfall and the testing uses black box testing. Conclusions students can choose a boarding house based on the SAW method that is in accordance with the specified krietria. Keywoard : SPK, Boarding House, SAW, Waterfall, Black box